Perform the indicated operation.
(x4)2

(x^4)^2 = x^8

Question

Asked 3/15/2016 12:55:45 PM

Updated 3/15/2016 2:59:47 PM

1 Answer/Comment

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

Rating

8

(x^4)^2 = x^8

Added 3/15/2016 2:59:47 PM

This answer has been confirmed as correct and helpful.

Factor this expression completely.
16x4 + 56x2 + 49 **Weegy:** 16x^4 + 56x^2 + 49; = (4x)^2 + 2*4x^2*7 + 7^2; = (4x^2 + 7)(4x^2 + 7); **User:** Perform the indicated operation.
6a2x(9a2 + 4bcx2 + 6abx) **Weegy:** 6a^2x(9a^2 + 4bcx^2 + 6abx)
= 54a^4x + 36a^3bx^2 + 24a^2bcx^3 **User:** Perform the indicated operation.
3a3x(4a2bcx3)
(More)

Question

Not Answered

Updated 3/11/2016 1:30:57 PM

1 Answer/Comment

3a^3x(4a^2bcx^3) = 12a^5bcx^4

Added 3/11/2016 1:30:57 PM

This answer has been confirmed as correct and helpful.

Factor this expression completely.
8r6 + 27s12
User: Perform the indicated operation.
(12x2 + 7y3)(4x2 + 7y3)
**Weegy:** (12x2 + 7y3)(4x2 + 7y3)
=48x4 + 84x2y3 + 28x2y3 + 49y6
=49y6 + 112x2y3 + 48x4 **User:** Factor this expression completely.
x2 - r2 **User:** Perform the indicated operation.
(r + s)(r2 - rs + s2) **User:** Perform the indicated operation.
(2a2 - 8)(4a4 + 16a2 + 64)
**User:** Perform the indicated operation.
(x4)2
(More)

Question

Updated 3/12/2016 10:41:45 AM

3 Answers/Comments

(r + s)(r^2 - rs + s^2)

= r^3 + sr^2 - r^2s - rs^2 + rs^2 + s^3

= r^3 + 0 + s^3

= r^3 + s^3

= r^3 + sr^2 - r^2s - rs^2 + rs^2 + s^3

= r^3 + 0 + s^3

= r^3 + s^3

Added 3/11/2016 7:10:16 PM

This answer has been confirmed as correct and helpful.

(2a^2 - 8)(4a^4 + 16a^2 + 64)

= 8a^6 - 32a^4 + 32a^4 - 128a^2 + 128a^2 - 512

= 8a^6 + 0 - 512

= 8a^6 - 512

= 8a^6 - 32a^4 + 32a^4 - 128a^2 + 128a^2 - 512

= 8a^6 + 0 - 512

= 8a^6 - 512

Added 3/11/2016 7:12:06 PM

This answer has been confirmed as correct and helpful.

Perform the indicated operation.
(2x + y)(3x2 + y) **Weegy:** (2x + a)(3x^2 + b) = 6x^3 + 2bx + 3ax^2 + ab; = ab + 3ax^2 + 2bx + 6x^3 (More)

Question

Updated 3/11/2016 1:36:46 PM

1 Answer/Comment

(2x + a)(3x^2 + b)

= (2x)(3x^2) + (2x)(b) + (a)(3x^2) + (a)(b)

= 3ax^2 + 6x^3 + ab + 2bx

= (2x)(3x^2) + (2x)(b) + (a)(3x^2) + (a)(b)

= 3ax^2 + 6x^3 + ab + 2bx

Added 3/11/2016 1:36:46 PM

This answer has been confirmed as correct and helpful.

Factor this expression completely.
6x2 - 13x - 28
**Weegy:** 6x^2 - 13x - 28 = (2x - 7)(3x + 4) **User:** Factor this expression completely.
18x4 + 12x2y + 2y2 **Weegy:** 18x^4 + 12x^2y + 2y^2 = 2(9x^4 + 6x^2 + y^2) = 2(3x^2 + y)^2 **User:** Factor this expression completely.
2x2 + 11x + 15 **Weegy:** 2x^2 + 11x + 15 = 3(2x + 5) + x(2x + 5); = (x + 3)(2x + 5) **User:** Perform the indicated operation.
(a + b)(a - b) **User:** Perform the indicated operation.
(14x3y2z)4
(More)

Question

Not Answered

Updated 3/12/2016 10:45:33 AM

2 Answers/Comments

(a + b)(a - b)

= a*a + b*a - a*b - b*b

= a^2 + ab - ab - b^2

= a^2 - b^2

= a*a + b*a - a*b - b*b

= a^2 + ab - ab - b^2

= a^2 - b^2

Added 3/11/2016 7:07:57 PM

This answer has been confirmed as correct and helpful.

39,080,612

questions answered

There are no comments.